Maternal antenatal multiple micronutrient supplementation for long-term health benefits in children: a systematic review and meta-analysis. Issue 1 (December 2016) - Devakumar, Delan; Fall, Caroline; Sachdev, Harshpal; Margetts, Barrie; Osmond, Clive; Wells, Jonathan; Costello, Anthony; Osrin, David
Abstract Background Multiple micronutrient supplementation for pregnant women reduces low birth weight and has been recommended in low- and middle-income countries (LMICs) to improve child survival, growth and health. We aimed to review the evidence from long-term follow-up studies of multiple micronutrient supplementation beginning in the later first or second trimester. Methods We searched systematically for follow-up reports from all trials in a 2015 Cochrane review of multiple micronutrient supplementation in pregnancy. The intervention comprised three or more micronutrients and the comparison group received iron (60 mg) and folic acid (400 μg), where possible. Median gestation of commencement varied from 9 to 23 weeks. Primary outcomes were offspring mortality, height, weight and head circumference, presented as unadjusted differences in means or proportions (intervention minus control). Secondary outcomes included other anthropometry, body composition, blood pressure, and cognitive and lung function. Results We found 20 follow-up reports from nine trials (including 88, 057 women recruited), six of which used the UNIMMAP supplement designed to provide recommended daily allowances. The age of follow-up ranged from 0 to 9 years. Data for mortality estimates were available from all trials. Meta-analysis showed no difference in mortality (risk difference –0.05 per 1000 livebirths; 95 % CI, –5.25 to 5.15). Six trials investigated anthropometry and found no difference at follow-up in weight-for-agez score (0.02; 95 % CI, –0.03 to 0.07), height-for-agez score (0.01; 95 % CI, –0.04 to 0.06), or head circumference (0.11 cm; 95 % CI, –0.03 to 0.26). No differences were seen in body composition, blood pressure, or respiratory outcomes. No consistent differences were seen in cognitive function scores. Conclusions There is currently no evidence that, compared with iron and folic acid supplementation, routine maternal antenatal multiple micronutrient supplementation improves childhood survival, growth, body composition, blood pressure, respiratory or cognitive outcomes.